Professional Learning and Development after the Active Learning Phase: Case Studies of New Zealand Schools - Santosuosso, Giordana Antonietta (Auckland University of Technology, 2025)
Internationally recognised as essential for enhancing education and ensuring sustainability across all levels of an educational organisation, professional learning and development is at the heart of effective teaching practice and the promotion of positive student outcomes. Therefore, it is reasonable to expect that schools implement effective processes to evaluate the impact(s) of professional learning and development on teachers, as well as the resultant effects on students’ learning outcomes. However, there remains a notable gap in comprehensive evidence from various studies that provide valid conclusions regarding the effectiveness of professional development, with only a few studies reporting the correlation between professional learning and development and improvements in student outcomes (Baird & Clark, 2018). The evaluation of the effects on professional learning and development is regarded as an ongoing process. During the active adult learning, evaluation should occur at multiple checkpoints to gauge its impact on both teachers and students. Consequently, it is imperative to investigate the space following the completion of the professional learning and development, considering mainly three key areas: firstly, how schools evaluate any sustained impacts of professional learning and development on teachers; secondly, which expectations schools have for reporting the outcomes of professional learning and development; and thirdly, which elements enable or hinder the effectiveness of professional learning and development in the workplace. Utilising a mixed methods research design, this study employs a sequential approach to data collection, incorporating both quantitative and qualitative results from a survey and semiconducted interviews with participants from three schools in Aotearoa New Zealand. The key findings reveal that design of professional learning and development partially aligns with frameworks suggested in the existing literature. Furthermore, follow-up processes are an integral recognised part of PLD design, school strategic goals are aligned with the PLD activities, and while improvements in student learning are perceived, they are not formally evaluated. The main barriers to effectiveness include the lack of sufficient time allocated to delve deeper into new learning and the need for differentiated learning opportunities. In response to these findings, this study offers recommendations for future PLD design aimed at bolstering the effectiveness of PLD in New Zealand schools. These recommendations advocate for the incorporation of established theories of professional learning into the design of programme, an expanded integration of teacher agency, and the implementation of a robust accountability system. By embedding thorough follow-up processes within the overall school structure, the effectiveness of learning, retention, and transformative changes in teaching practices may be significantly enhanced over time. Additionally, providing longitudinal evidence of the effectiveness of new practices would greatly benefit the planning of targeted Professional Learning and Development in schools, the refinement of models and framework of PLD in the domain of follow-up by the research community, and policy makers in the educational context.